Does Opinion Shopping Impair Auditor Independence and Audit Quality? - LU, TONG (Journal of Accounting Research, 2006)
This study investigates how companies' threats to dismiss auditors and their engagement in opinion shopping influence auditor independence and audit quality, which in turn affect misstatements in financial statements. It also examines how outsiders' reactions to auditor switching influence opinion shopping. The results indicate that neither the predecessor auditor's nor the successor auditor's independence is compromised by dismissal threats and opinion shopping. Further, the successor auditor's audit quality exceeds the predecessor auditor's audit quality. In addition, auditor switching decreases potential understatements and increases potential overstatements in financial statements, and the capital market's and the successor auditor's reactions to auditor switching reduce the benefits of opinion shopping to companies. Additionally, the study sheds some light on the potential effects of both the Sarbanes-Oxley's restriction on non-audit services and mandatory auditor rotation or retention. The paper also derives a rich set of empirical implications.